PENGARUH KONSENTRASI DAN LAMA PERENDAMAN KAYU SENGON (Paraserianthes falcataria L. Nielsen) DALAM EKSTRAK DAUN SIRSAK (Annona muricata L.) TERHADAP SERANGAN RAYAP TANAH (Coptotermes sp.) - Ardiansa, Budi; Ariyanti, Ariyanti; Hapid, Abdul (Warta Rimba, 2014)
Wood has many contribution for life. It can be useful for bueldings, huose ware, and for other using. The use of wood are followed by huma needs for manufactured wood in creasingly, while long life wood tend to be more scarce and higher in price. This research aims to know the influence of the concentration and the immersion time for sengon wood treated in extracted soursop leaf to defence from subterranean termite. This research was conducted in both forestry Laboratorium, Departement and faculty of forestry, University of Tadulako and in rural of Baiya, Distict of Tawaely. Starting from Desember 2013 till Februari 2014. This research used a complete randomized factorial design. The first factor was the concentration of extracted soursop leaf (A) was 4.76% (A1), 13.04% (A2) and 16.66% (A3). The second factor was the immersion time for sengon wood treated in extracted soursop leaf (B) was 5 days (B1), 10 days (B2), and 15 days (B3). The results show that the highest of losing weight is in the control (A0B1) with 3.3%, and the lowest of losing weight is in the concentration of 150g with 10 days immersion (A1B2) with 1.21%. The concentration of extracted soursop leaf and the immertion time of sengon wood did not significantly influence to the lose of weight in tested sample. Keywords: Concentration, Dipping, Paraserianthes falcataria L. Nielsen, Annona muricata L, Coptotermes sp.